Fracture Mechanics of Ceramics Active Materials, Nanoscale Materials, Composites, Glass, and Fundamentals - Bradt, R.C.; Bradt, R.C.; Munz, D.; Munz, D.; Sakai, M.; Sakai, M.; White, Ken W.; White, Ken W. (Fracture Mechanics of Ceramics, 2005)
The 8th International Symposium on fracture mechanics of ceramics was held in on the campus of the University of Houston, Houston, TX, USA, on February 25-28, 2003. With the natural maturing of the fields of structural ceramics, this symposium focused on nano-scale materials, composites, thin films and coatings as well as glass. The symposium also addressed new issues on fundamentals of fracture mechanics and contact mechanics, and a session on reliability and standardization.